Implementasi Model Project Based Learning Berbasis Teori Belajar Kolaboratif dalam Pembelajaran Konsep Dasar IPA SD - Muhammad Ilham S.; Amri Amal (Program Studi PGSD Universitas Madako Tolitoli, 2023)
Students will get a more interesting and productive learning experience by using a project-based learning model based on collaborative learning theory. Students can better understand the basic concepts of elementary science, including the ability to work together and communicate. In the Basic Concepts of Science course, this research aims to explain how the project-based learning model, which is based on collaborative learning theory, can be applied. The study used descriptive methodology and involved 76 students. Data was collected by looking at how students learn. The results showed that PGSD students may better understand the concepts and better collaborate if a project-based learning model is applied to the Basic Concepts of Science course, making a project plan, making creative products, conducting self-evaluation and providing feedback, and discovering whether ideas are good or bad for everyday life.